Schools, Leadership and Gender A Study on Women School Leaders in Kerala Schools - Bakshi, Shivani (JOURNAL OF INDIAN EDUCATION, 2022)
With the advancement of professional prospects for women globally, top positions are now open and accessible to women across the professional arenas. School leadership is one such professional zone where women’s participation as school leaders is emerging firmly as ever before. Since women contribute as a major and defining workforce in Indian schools as teachers (MHRD, 2018), it becomes apparent and reasonable to have more females as school leaders. However, process of this emergence of females as school face many challenges during their role transformations. They sustain the administration and management-related impediments and fight a distinct war of the patriarchal mindset that questions their calibre of delivering results. The paper presents a case study from Kerala’s field experience under the doctoral thesis. Using an in-depth interview schedule under qualitative research methodology, the cases portray the journey of two women leaders’ in the schools situated in Trivandrum and Quillon, respectively. The study engages in a dialogue in women’s leadership where the dynamics operate in a tight bureaucratic setup tinted with patriarchy shades. It questions the legitimacy of gendering the concept of school leadership and the implications drawn for the Indian school system.